2015
DOI: 10.1016/j.foodres.2014.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effect of pH, sodium chloride and sodium pyrophosphate on the thermal resistance of Escherichia coli O157:H7 in ground beef

Abstract: The objective of this study was to assess the combined effects of temperature, pH, sodium chloride (NaCl), and sodium pyrophosphate (SPP) on the heat resistance of Escherichia coli O157:H7 in minced beef meat. A fractional factorial design consisted of four internal temperatures (55.0, 57.5, 60.0 and 62.5°C), five concentrations of NaCl (0.0, 1.5, 3.0, 4.5 and 6.0 wt/wt.%) and SPP (0.0, 0.1, 0.15, 0.2 and 0.3 wt/wt.%), and five levels of pH (4.0, 5.0, 6.0, 7.0 and 8.0). The 38 variable combinations were replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…The effect of NaCl addition on solute accumulation and heat resistance of E. coli is observed at concentrations that are typical for food systems. A critical concentration of NaCl in ground beef, about 2.7-4.7%, substantially increased heat resistance of E. coli O157:H7 at 55-62.5°C (Juneja et al, 2015). In addition, pre-exposure to 5% NaCl at room temperature for 24 h increased the heat resistance of E. coli O157:H7 at 55°C (Bae and Lee, 2010).…”
Section: Effects Of Salt or Sugar Addition In High Moisture Foodsmentioning
confidence: 99%
“…The effect of NaCl addition on solute accumulation and heat resistance of E. coli is observed at concentrations that are typical for food systems. A critical concentration of NaCl in ground beef, about 2.7-4.7%, substantially increased heat resistance of E. coli O157:H7 at 55-62.5°C (Juneja et al, 2015). In addition, pre-exposure to 5% NaCl at room temperature for 24 h increased the heat resistance of E. coli O157:H7 at 55°C (Bae and Lee, 2010).…”
Section: Effects Of Salt or Sugar Addition In High Moisture Foodsmentioning
confidence: 99%
“…Values used were initial sachet temperature = 4°C, heat-up target temperature = 58.165°C (i.e., 99% of 58.75), sachet thickness = 0.0005 m (=½ × 1 mm thickness), and for the ground beef, (Pan & Singh, 2001) thermal conductivity = 0.38 W m −1°C−1 , density 5 = 1019.5 kg m −3 , specific heat (Anon., 1972) = 3520 J kg −1°C−1 , and water-bath heat transfer coefficient (Bedecarrats, Strub & Peuvrel, 2009;Anon., 2015) = 500 W m −2°C−1 . (Large changes in the value of the heat transfer coefficient for heating and cooling over the range of water temperatures reported by Juneja et al (2015) can be demonstrated to not meaningfully affect predicted heat-up times (Davey, 2015)). 4.…”
mentioning
confidence: 94%
“…We acknowledge that the work of Juneja et al (2015) possibly represents very valuable data for a major pathogen. However we wish to draw attention to the following:…”
mentioning
confidence: 99%
“…Ohmic heating has been used to inactivate Escherichia coli O157:H7, Salmonella Typhimurium and Listeria monocytogenes in orange and tomato juice [19]. Populations of foodborne pathogens during heat treatment change with heating temperature, water activity (a w ), heating rate, pH, heat shock, recovery medium and composition/physical characteristics of the foods [20][21][22][23][24][25][26][27]. For example, when the ground beef inoculated with Escherichia coli O157:H7 was cooked in a water bath for 1 h at temperature of 55-62.5 C, the D-value (the time required at a certain temperature to reduce a specific microbial population by 90% or by a factor of 10) was significantly lower in ground beef adjusted with pH 4.5 than pH 5.5 [22].…”
Section: Introductionmentioning
confidence: 99%
“…under conventional and novel thermal technologies are reviewed but only the primary model (the food-borne pathogen evolution as a function of heating time) is concerned [28]. However, since the inactivation kinetics are actually influenced by several factors, such as different bacterial strains, age of the culture, food composition (fat, NaCl, pH and a w ), processing parameters, and physiological state of the organisms, some researchers have established secondary models for predicting survival curves under different conditions [20,24,[29][30][31][32]. Also omnibus models incorporating the primary and the secondary models are further considered for predicting survival curves of pathogens [23,33,34].…”
Section: Introductionmentioning
confidence: 99%